1995
DOI: 10.1021/jm00020a025
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antiviral Activity of Certain 2,5,6-Trihalo-1-(.beta.-D-ribofuranosyl)benzimidazoles

Abstract: A new series of 2-substituted 5,6-dichlorobenzimidazole ribonucleosides has been synthesized and tested for activity against two human herpes viruses and for cytotoxicity. 2,5,6-Trichloro-1-(beta-D-ribofuranosyl)benzimidazole (TCRB) was prepared by ribosylation of the heterocycle 2,5,6-trichlorobenzimidazole followed by a removal of the protecting groups. The 2-bromo derivative (BDCRB) was made in a similar fashion from 2-bromo-5,6-dichlorobenzimidazole. In contrast, the 2-iodo derivative presented a more diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
201
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(211 citation statements)
references
References 16 publications
8
201
2
Order By: Relevance
“…BDCRB was synthesized in the laboratory of L. B. Townsend as previously described (34). Maribavir was synthesized at GlaxoSmithKline (22) and was provided through the courtesy of K. K. Biron.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BDCRB was synthesized in the laboratory of L. B. Townsend as previously described (34). Maribavir was synthesized at GlaxoSmithKline (22) and was provided through the courtesy of K. K. Biron.…”
Section: Methodsmentioning
confidence: 99%
“…In 1995, we reported the synthesis and antiviral activity of TCRB and its 2-bromo analog, BDCRB (34) (Fig. 1).…”
mentioning
confidence: 99%
“…Thus, mapping of benzimidazole ribonucleoside resistance to packaging genes is consistent with the observed inhibition An evaluation of data from a number of antiviral susceptibility assays in our laboratory suggested HCMV strain AD169 was more sensitive to the benzimidazole ribonucleosides than HCMV strain Towne. The assays were performed as previously described (Townsend et al, 1995). Briefly, HFF cells in 24-well cluster dishes were infected with approximately 100 p.f.u.…”
mentioning
confidence: 99%
“…[5][6][7] Multiple previous reports have suggested that benzimidazoles to be very good cytotoxic agents against different types of cancer cell lines. 8 Recently bisbenzimidazole conjugates have been reported to target mitochondria in cancer cells and induce their antiproliferative activity by caspase dependent apoptosis.…”
Section: Introductionmentioning
confidence: 99%